Preliminary assessment of microplastic pollution in commercial freshwater fish species collected from four districts in Bac Ninh province - Mai, Huong; Ngo, Thi Thao Nhi; Nguyen, Danh Thien; Bui, Van Hoi; Dao, Thanh Duong; Dang, Thi Thom; Do, Van Manh (Vietnam Journal of Science and Technology, 2023)
Microplastics (MPs) are of emerging widespread concern, but amount of research done in freshwater environments and organisms is scarce compared to that in marine environments. Thus, the MPs identification in four freshwater fish at four districts of Bac Ninh province were documented, including common carp (Cyprynus carpio), grass carp (Ctenopharyngodon idella), tilapia (Oreochromis niloticus), and red-tilapia (Oreochromis sp.). MPs were found in the gastrointestinal tracts (GIT) of 100% of examined fish. MPs abundances have significant differences between all freshwater fish collected from ponds and local markets (except for red-tilapia), while no difference by individual of each species neither in pond nor in local markets. The median sizes of microplastics ranged from 1410 µm to 2706 µm. The MPs were dominated by purple in color (in pond with average 38%; in local market with average 33%). µ-FTIR analysis showed that polymers found in fish GIT mainly were polyethylene terephthalate, polyethylene, polypropylene and nylon. These results showed that the microplastics was widely ingested by freshwater fish and help to aware people which fish are more contaminated with MPs to human consumption in Bac Ninh province.